Medidas e modelagem do transporte de água e osmorregulação em células renais individuais usando pinça óptica e videomicroscopia - Aline Duarte Lucio (2003)
Water transport is an essential process in any cell. We developed a technique that allows us to measure water transport in a single isolated cell under osmotic shock, using optical tweezers and videomicroscopy. We use a well-studied kidney cell (MDCK) for the experiments. The use of optical tweezers together with videomicroscopy allowed us to directly measure cell volume variation as a function of time, and clearly observe the out°ow of water due to osmotic up-shock and the subsequent in°ow of water due to regulation processes, without the interaction withother cells or substract. Since in the literature there is no model of water transport in cells that takes into account cellular volume regulation, we propose in this work a phenomenological model of transport that takes volume regulation into account and that ¯ts very well our experimental observations. From our model, two time scales appear naturally: a fast one related to transport of water and a slow one related to transport of solutes towards osmotically active regions that is responsible for cellular volume regulation. Therefore, in our experiments we are able to obtain in addition to water permeability, the solute in°ux rate for cellular volume regulation and the regulatory volume (cell volume after regulation), parameters not measured before and that seem important to properly analyze the e®ects of hormones and drugs on cells, as evidenced by our measurements with the addition of the anti-diuretic hormone or arginine-vasopressin.